Pembelajaran Fisika dengan Model Siklus Belajar 5-E (Engage, Explore, Explain, Elaborate, Evaluate) sebagai Upaya Meningkatkan Kecakapan Hidup Siswa - Hikmawati Hikmawati (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
Life skills of students and teachers in the Province of West Nusa Tenggara, especially the island of Lombok is still low. Development of life skills is not optimal attention of government and education observers. Life Skills is a skill that must have to dare to face the problems of life and everyday life with a reasonable without feeling depressed, then proactively and creatively search for and find a solution so as to cope. Life skills can be developed through classroom learning, including learning physics. Physics should be viewed as a process and at the same time so that the product in physics learning two things must be taken into consideration in choosing a model of learning that the learning process can be both effective and efficient. Application of the learning cycle model of 5-E (Engage, Explore, Explain, Elaborate, Evaluate) may be an alternative for teachers to achieve the expected learning goals. This model can facilitate active learning in exploratory activities through interaction with the teacher, as well as with other students. Thus, the application of the learning cycle model of 5-E in learning physics is expected to increase students' life skills